(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article highlights the psychological interpretation of cyberattack prevention. Also, the use of prevention from cyber attacks as a research subject of psychology and as a criterion determining the main essence in psychological research is analyzed.